The Influence of Information Technology, Social Media and Knowledge Management on Employee Performance - Indra Bratamanggala, Rieki (Siber International Journal of Education Technology (SIJET), 2023)
Literature review is a process of investigating and understanding various previous research results that have been published by researchers. This activity is useful for increasing understanding of the research topic being undertaken. Previous research and relevant research have an important role in forming a comprehensive literature review. Findings from previous research and appropriate research strengthen the theoretical basis, conceptions, and phenomena that have an impact on variable development. In this article, the results of a literature review are presented regarding factors that influence performance in a company. These factors include information technology, social media, knowledge management, as well as literature studies related to Executive Support Systems (ESS) for business. The results of this literature review include: (1) Information Technology influences employee performance; (2) The influence of social media on employee performance; and (3) the influence of Knowledge Management on employee performance.